Post-synthetically modified MOF for the A3-coupling reaction of aldehyde, amine, and alkyne - Kassymova, Meruyert; de Mahieu, Alaric; Chaemchuen, Somboon; Demeyere, Patrick; Mousavi, Bibimaryam; Zhuiykov, Serge; Yusubov, Mekhman S; Verpoort, Francis (Catalysis science & technology, 2018)
A new heterogeneous NHC catalyst (Ag-NHC-MOF) was synthesized by the post-synthetic modification of an azolium-containing metal–organic framework. The structure of the catalyst was well defined and fully characterized using various techniques such as PXRD, FE-SEM, HR-TEM, XPS, FT-IR, TGA, BET, 1H-NMR, 13C-NMR, EDS, and ICP. The catalyst showed an excellent activity towards the A3-coupling reaction with a broad substrate scope. The A3-coupling reaction was performed under ambient conditions and full conversion was reached within just 1 hour for the model reaction. The heterogeneous silver NHC MOF (Ag-NHC-MOF) catalyst can be recycled and reused at least four times without a significant loss of activity. In comparison with previously reported heterogeneous catalysts applied for the A3-coupling reaction, the Ag-NHC-MOF demonstrates a superior performance for the A3-coupling reaction.